Estudos das propriedades magnéticas e caracterização estrutural da hexaferrita de estrôncio com substituição de Fe2O3 por Mn2O3 - Nasser, Hanilton Marana (2017)
The present work is aimed at the synthesis, structural and magnetic characterization of strontium hexaferrite (SrFe12O19), besides demonstrating variation in the magnetic properties generated by the substitution of Fe3+ cation by the Mn3+ cation. The samples were obtained by the solid-state process and calcined at 1200 ° C for 4 hours and were performed by the following chemical formula: SrFe12-xMnxO19 (0 ≤ X ≤ 5). The characterization was performed by the X-ray diffraction process, and the magnetic properties were demonstrated by magnetic hysteresis tests by the Vibrant Sample Magnetometer principle. The different concentrations of Mn3+ resulted from significant variation in both the network parameters and the magnetic properties.